RELATIONSHIP OF PERSONAL SELF-ASSESSMENT (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article analyzes the concepts of self-esteem of the individual, the mechanisms of psychological defense, considers and analyzes approaches to this problem.